The Concept of Intellectual Property As Al Mal: An Islamic Perpective Approach - Mohd Arif , Mohd Izzat Amsyar; Hanapi, Hisham (International Journal of Educational Best Practices, 2017)
The idea of legally acknowledging and protecting the intellectual property is prevalently known in any legal system in the world, but not many people know how this idea is dealt in Islam. Islam as the religion of wholeness (syumul), deals with almost all aspects of life and aims at protecting five main objectives of syariah3 (maqasid al syariah) namely religion (al din), life (al nafs), intellect (al aqal), lineage (al nasl) as well as property (al mal). As the time goes by, people started to realize that human intelligence and creativity shall not be the object of manipulation, thus necessitated them to come up with some sort of protection for their invention by legally acknowledging it as ‘intellectual property’. This paper will try to discuss the position of intellectual property in the Islamic jurisprudence by determining its ‘maaliyyah’ (capable of being considered as property).